Stationary behaviour of observables after a quantum quench in the spin-1/2 Heisenberg XXZ chain - Fagotti, M; Essler, F (2013)
We consider a quantum quench in the spin-1/2 Heisenberg XXZ chain. At late times after the quench it is believed that the expectation values of local operators approach time-independent values, that are described by a generalized Gibbs ensemble. Employing a quantum transfer matrix approach we show how to determine short-range correlation functions in such generalized Gibbs ensembles for a class of initial states.